Methodological basis of Black Locust (Robinia pseudoacacia L.) regeneration by coppicing: case studies - Keserű, Zsolt; Ábri, Tamás; Honfy, Veronika; Rédei, Károly (Acta Agraria Debreceniensis, 2025)
In countries struggling with timber shortage, including Hungary, fast-growing tree species such as black locust (Robinia pseudoacacia L.) offer the possibility of meeting an increasing proportion of timber demand from domestic sources through more efficient use of cultivation opportunities. Coppice forest management is the oldest, but also the simplest and, in most cases, the most cost-effective method of operation. In this paper, we present the timber production criteria for the coppice regeneration method, including the accelerated determination of the timber stock of black locust parent stands through case studies.